A Survey on Differences in Implementing Evidence-Based Practice According to Five Psychotherapist Variables - Middleton, Jerry C.; Azzi, Michelle; Watkins-Martin, Kia; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2025)
Given the divide between research and practice, there has been an increased focus on evidence-based practice (EBP) in psychology. EBP has been defined as the integration of three main components during clinical decision-making: (a) best available research evidence, (b) clinical expertise, and (c) client characteristics, cultures, and treatment preferences. However, little is known about the self-ratings of implementing EBP or its components among psychotherapy providers. Secondary data analyses of a survey of Canadian psychotherapy providers (Middleton et al., 2020) investigated differences in providers’ self-ratings of implementing EBP according to five psychotherapist variables. These psychotherapist variables included the primary therapeutic approach, the number of years of professional experience, the primary setting of practice, the level of education, and the professional capacity of practice. Results indicated significant results for many psychotherapist variables. Among other findings, while psychotherapy providers who were oriented primarily toward cognitive and/or behavioural approaches had significantly higher self-ratings of implementing EBP than did those with a psychoanalytic/psychodynamic approach, providers with a master’s degree had significantly lower self-ratings than did those with a Ph.D. or with postdoctoral training. Findings are discussed in relation to educational, research, and training initiatives in EBP.